Places of Information Generation: Bridging Pannenberg's Logos and Deacon's Emerging Semiosis. Issue 3 (2nd July 2016) - Graves, Mark
ABSTRACT: Bridging Wolfhart Pannenberg's comprehensive twentieth-century systematic theology of Creation and Terrence Deacon's very thorough scientific account of material and biological development and evolution results in an integrative view of Creation from Trinitarian relationality to biomolecular processes. Pannenberg's understanding of Logos guides the investigation of the progressive unfolding of forms toward the key construct of information generation which Deacon's theory of emergence explains as selection dynamics. Modeling both space and form as a place where activity generates information synthesizes Pannenberg's complementary activities of Logos and Spirit with Deacon's emergent dynamics and semiosis to develop generative distinctions among a field of systems as a key component of a scientifically plausible theological anthropology.